Ordered response models for sovereign debt ratings - Afonso, António (2006)
Using ordered logit and probit plus random effects ordered probit approaches, we study the determinants of sovereign debt ratings. We found that the last procedure is the best for panel data as it takes into account the additional cross-section error.